Gambaran Entrepreneurial Skill dan Business Success pada Pengusaha - B Lena Nuryanti; Dian Herdiana Utama; Rizky Wirayuda (Business Education Program of Universitas Pendidikan Indonesia, 2020)
The purpose of this study is to study the perceptions of entrepreneurs regarding the use of entrepreneurial skill and business success. The survey was conducted at the Entrepreneur of Benua Citra Niaga (BCN) in Bandung with a population of 151 entrepreneurs. The results of the study using a questionnaire revealed business research and business success in BCN in Bandung depending on the category which is quite good, it can be attributed to large respondents who can implement entrepreneurial skill better with better business success.. Business processes at the SMEs scale are expected to use entrepreneurial skill more intensively so as to enhance business success..